Pengaruh Kepemimpinan dan Pemberdayaan Terhadap Produktivitas Dosen Bidang Penelitian di Universitas Brawijaya - Sudjari, Sudjari (Jurnal Administrasi Publik, 2017)
Lecturers as professional workers are required to improve their productivity through four aspects, they are: (1) implement leadership and teaching, (2) conduct research, (3) carry out community service and (4) lecturers’ activities support. Empowerment implies that the potential within every lecturer can be used optimally. This research is conducted with 107 lecturers in University of Brawijaya. Data is analyzed through path analysis to prove the correlation between the leadership with the productivity of lecturers mediated by empowering of lecturer. The results of this research is the leadership and empowerment significantly effect the productivity of lecturers. Lecturers’ empowerment proven able to mediate between leadership with lecturers’ productivity.